PEMETAAN TINDAK KRIMINALITAS DI KOTA PALOPO TAHUN 2015 - Lestari, Alia; Aswad A, Muhammad Hajarul (Lembaga Penelitian dan Pengabdian pada Masyarakat (LP2M) IAIN Palopo, 2016)
The crime occurred in Palopo city each year is volatile enough. Although they tend to fall through leaving 176 cases in 2013, it does not mean that Palopo is fairly safe from the criminal acts. The societies of Palopo especially the polices, it is very important to know the areas included in the crime-prone areas. Therefore, this study tried to map the crimes occurred in Palopo city by applying Correspondence Analysis. The research objects were criminal data reported in the police of Palopo City since January to September 2015. From Chi-Square analysis, it was found that there was a relationship between the variables of Criminal Action Types and Occurrence Time. Similarly, the Criminal Action Types with Occurrence Places, and Criminal Action Types by the reasons occurring Criminal Acts also showed a relationship with criminal acts against the place and the reasons for the crimes. Furthermore, based on the correspondence analysis it was found that the largest crimes in the area of the police of Palopo are the theft of the motorcycles and the smallest crimes are persecutions. Most of time incidents occurred at 24.00-07.00. The crimes occurred in Wara district